STRUKTUR DAN TEKSTUR DRAMA KABALE UND LIEBE KARYA FRIEDRICH SCHILLER - HIDAYAHTULLOH, PUTRI (IDENTITAET, 2017)
Drama has two dimensions that can be enjoyed and appreciated. There are literature dimensions and show dimension (Hassanudin in Dewojati, 2010:8). The beautiful drama built from the structure and texture. Therefore, research question posed in this research is  (1) how is the structures in drama Kabale und Liebe by Friedrich Schiller and (2) how is the texture in drama Kabale und Liebe by Friedrich Schiller. This research aimed to (1) describe the structure of drama Kabale und Liebe by Friedrich Schiller and (2) describe the texture of drama Kabale und Liebe by Friedrich Schiller. This research uses Kernodle drama structure and texture theory. Structure of drama consists of plot, character and theme, and texture consists of dialogue, mood and spectacle. This research use qualitative desciptive research. The source of this research data is the script of drama Kabale und Liebe. Technique of read notes is used to collect data in the form of dialogue, words or phrases that contain elements of structure and texture. Results of the research about structure and texture of drama Kabale und Liebe is plot the story ended tragically with the death of the main Character. Character is divided into two type, there are Hauptcharakter (main characters) namely Luise and Ferdinand and Nebencharakter (supporting characters)   namely   President,   Miller,   Frau,   Wurm,   Lady   Milford,   Hofmarshall,   Sophie   and Kammerdiener. Then the theme is a love story that ended tragically because of differences social status. Kabale und Liebe drama has 4 monologues by Luise (1), Ferdinand (3), Lady Milford (1). Mood that displayed in each round of the atmosphere is tension, but there is also an atmosphere of restlessness, sadness, emotion, annoyance, worry and regret. The Spectacle shows that this drama does not require a complicated stage setting and does not use many properties to support the storyline. Keyword: Drama, Structure, Texture.